Analyzing the Connection between Energy Prices and Cryptocurrency throughout the Pandemic Period - Nurkhodzha Akbulaev; Tural Abdulhasanov (International Journal of Energy Economics and Policy, 2023)
Today's discussion centers on whether cryptocurrencies may be used to pay for products and services in developed and underdeveloped nations. The role of cryptocurrencies as investment and speculative trading vehicles is also expanding. The cryptocurrency bitcoin serves as an illustration of such use. The first cryptocurrency to develop value without initially satisfying requirements and carrying any type of collateral in the form of traditional currencies is bitcoin. The analysis of the variables influencing the price of bitcoin is one of the most hotly debated subjects in the financial literature. The purpose of this study is to look into the connection between the price of natural gas and crude oil and the cryptocurrency Bitcoin. In this study, the effect of Brent oil, crude oil and natural gas prices on Bitcoin was examined. For the data containing the weekly time series for the period 05.01.2020-26.12.2021, FMOLS and DOLS tests were conducted, which show the coefficient of cointegration, causality and relationship. According to the findings of the study, according to the FMOLS test, 1% Bitcoin in brent oil price increases 0.000176% (probability values according to DOLS do not confirm the effect). Likewise, when we look at crude oil, according to FMOLS test, 1% Bitcoin in crude oil price increases 0.000180% (the probability values according to DOLS do not confirm the effect). When we look at the changes in the Bitcoin price, according to the DOLS test, a 1% increase in the Bitcoin price increases the Brent oil by 77.86132% (the probability values according to FMOLS do not confirm the effect).